2012
DOI: 10.1007/s00421-012-2379-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical determinants of 100-m sprint running performance

Abstract: Sprint mechanics and field 100-m performances were tested in 13 subjects including 9 non-specialists, 3 French national-level sprinters and a world-class sprinter, to further study the mechanical factors associated with sprint performance. 6-s sprints performed on an instrumented treadmill allowed continuous recording of step kinematics, ground reaction forces (GRF), and belt velocity and computation of mechanical power output and linear force-velocity relationships. An index of the force application technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
341
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(419 citation statements)
references
References 47 publications
31
341
2
7
Order By: Relevance
“…The results indicated that there were no significant changes in the best potentiated sprint performance relative to the baseline for any sprint interval following either PAP condition. Sprint acceleration requires great force be produced to overcome the inertia of an individual's body mass [22], with a particular importance for horizontal force production [26]. The force generated during the WL may not have been sufficient to potentiate 20-m sprint performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that there were no significant changes in the best potentiated sprint performance relative to the baseline for any sprint interval following either PAP condition. Sprint acceleration requires great force be produced to overcome the inertia of an individual's body mass [22], with a particular importance for horizontal force production [26]. The force generated during the WL may not have been sufficient to potentiate 20-m sprint performance.…”
Section: Discussionmentioning
confidence: 99%
“…Yetter and Moir [16] stated that an exercise such as a back squat may not provide a movement-specific stimulation to the muscles required for sprint acceleration due to the different mechanical demands of acceleration versus maximal velocity sprinting. As sprint acceleration places a greater emphasis on horizontal force as opposed to vertical force [26], a strength exercise that features a horizontal component such as a walking lunge (WL) [25,27] may be better suited to providing a PAP effect. However, no research has investigated if the WL is an appropriate exercise to potentiate sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the mechanics of linear sprinting, with the majority focusing on spatiotemporal variables. The fastest runners maximize their acceleration and maximum sprinting velocities by applying greater mass-specific ground forces, [1][2][3] but research literature has so far provided limited information regarding how sprinting athletes should optimize their movements. Due to technology limitations, experimental kinematic studies have typically focused on the measurement area either around the start, [4][5][6] the acceleration phase [7][8][9][10] or during the maximal velocity phase, [11][12][13] typically assessing 1-3 steps.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown high levels of horizontal force application is related to faster sprinting speeds. [11][12][13][14][15] Contreras and colleagues 16 found that the hip thrust is effective for improving both horizontal jump distance and sprinting performance.…”
Section: Introductionmentioning
confidence: 99%